**Introduction:**

Trigonometric formulas used to express the trigonometric functions. Trigonometric individuality and formulas are based on trigonometric functions. The essential trigonometric functions are Sine, Cosine and tangent functions of a triangle takes an angle and give the sides of the triangle. Where the sin takes an angle and gives the length of the y component. Cosine role takes an angle and gives the x component length. Similarly the Tan value takes an angle and gives the slope of the triangle.

## Formulas on trigonometric formulas learning

First we have to learn the basic functions which are used in trigonometric formulas

Sin rate of the angle = opposed / Hypotenuse

Cos assessment of the angle = Adjacent / Hypotenuse

Tan of the angle = Opposite / Adjacent

## Formulas on trigonometric formulas learning

There are totally five types of trigonometric formulas,

1. Sum and difference formula

2. Double Angle Formula

3. Triple angle Formula

4. Half angle formulas

5. Sum of product formulas

I am planning to write more post on Special Parallelograms with example, Corresponding Parts of Congruent Triangles. Keep checking my blog.

**Learning of Sum and Difference formulas:**

Cos (A+B) = Cos A Cos B – Sin A Sin B

Cos (A-B) = Cos A Cos B + Sin A Sin B

Sin (A+B) = Sin A Cos B + Cos A Sin B

Sin (A-B) = Sin A Cos B- Cos A Sin B

Tan (A+B) = (Tan A + Tan B) / (1 – TanA tanB)

Tan (A-B) = (TanA- TanB) / (1+TanA TanB)

**Learning of ****Double Angle Formula:**

Sin2A = 2 Sin A Cos A

Cos 2A = Cos^{2}A – Sin^{2}A

Cos 2A = 1 – 2Sin^{2} A

Cos 2A = 2Cos2A – 1

Tan 2A = 2 Tan A / (1 – Tan2 A)

**Learning of ****Triple Angle Formulas:**

Tan 3A = (3 Tan A – Tan^{3}A) / (1 – 3 Tan^{2} A)

Sin 3A = 3 Sin A – 4Sin^{3}A

Cos 3A = 4Cos^{3}A – 3 Cos A

**Learning of ****Half Angle Formulas**

Sin2 (A / 2) = (1 – Cos A) / 2

Cos2 (A / 2) = (1 + Cos A) / 2

Tan2 (A / 2) = ((1 – Cos A) / 2) / ((1 + Cos A) / 2)

**Learning of ****Product of Sum Formulas:**

Sin A Sin B = [Cos (A - B) - Cos (A+B)] / 2

Sin A Sin B = [Cos (A - B) + Cos (A+B)] / 2

Sin A Cos B = [Sin (A - B) + Sin (A+B)] / 2